Sistem Kontrol Irigasi Sprinkler Otomatis Bertenaga Surya di Kelompok Tani Kecamatan Meureubo Kabupaten Aceh Barat - Sudirman Sirait; Sri Maryati (Balai Teknik Irigasi, 2018)
The application of automatic sprinkler irrigation technology powered by solar panel can be designed by utilizing digital technology, microcontroller and sensor network. The aims of this research are to analyze the performance of solar powered automatic sprinkler irrigation control systems on the experimental field. This research was divided into several stages, which are the analysis of experimental land, the design of automatic control systems and the sprinkler irrigation system, the field testing and application, and the performance analysis of automatic sprinkler irrigation. The Arduino Uno ATMega328P microcontroller was used as an automatic control system for the on-off arrangement of irrigation pumps based on soil moisture detected by the YL-69 soil moisture sensor. Based on the results of analysis of soil water content, soil moisture arrangement level of 13.58% as the lower set point value and 28.29% as the upper set point value for reference on irrigation pump on-off control can keep the soil moisture from the water capacity. This technology was powered using solar power consisting of a 30 Wp solar panel, solar charge controller, inverter and battery series therefore it can be operated 24 hours continuously for 7 days. The results showed that the maximum soil water content value was 29.10%, minimum soil water content value was 12.87% and the average soil water content value was 23.55%. The average of time for irrigation pump operation was 13.07 minutes with the total irrigation application was 21.40 m3. The total power to operate an automatic sprinkler irrigation system of 67.0 Watt and can reduce battery consumption of 234.7 Watt.